2015
DOI: 10.3389/fnhum.2015.00194
|View full text |Cite
|
Sign up to set email alerts
|

Neural Connectivity in Epilepsy as Measured by Granger Causality

Abstract: Epilepsy is a chronic neurological disorder characterized by repeated seizures or excessive electrical discharges in a group of brain cells. Prevalence rates include about 50 million people worldwide and 10% of all people have at least one seizure at one time in their lives. Connectivity models of epilepsy serve to provide a deeper understanding of the processes that control and regulate seizure activity. These models have received initial support and have included measures of EEG, MEG, and MRI connectivity. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 37 publications
(47 reference statements)
1
30
0
Order By: Relevance
“…It has been tested in previous studied specifically in estimating epilepsy network nodes [31], [32], [84], [85]. Other networks like the pain network have also been studied using combined ESI and ADTF analysis [86].…”
Section: Discussionmentioning
confidence: 99%
“…It has been tested in previous studied specifically in estimating epilepsy network nodes [31], [32], [84], [85]. Other networks like the pain network have also been studied using combined ESI and ADTF analysis [86].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, Granger Causality analysis (GC) was used to determine the directed causal dependencies of brain regions from the EEG signal. GC is a method for investigating whether one time-series correctly predicts another and allows us to analyze brain circuit connections and how they change over the course of a cognitive process (Coben and Mohammad-Rezazadeh, 2015). We hypothesized that, similar to Scharinger et al (2015), an increase in updating load would affect both behavioral and neurophysiological measures and these metrics would be modulated by individual working memory capacity (i.e., OSPAN score).…”
Section: Introductionmentioning
confidence: 99%
“…26 In this study, we used effective connectivity analysis and found a statistically significant effective connectivity of the limbic network in TLE patients with HS, especially through the thalamus, in contrast to TLE patients without HS and normal controls. Effective connectivity analyzes the direction, interaction, and causality between two regions, and it can be used to understand causal relationships between entities in the brain network.…”
Section: Discussionmentioning
confidence: 94%